A majority gate with chiral magnetic solitons. (24th August 2018) - Koumpouras, Konstantinos; Yudin, Dmitry; Adelmann, Christoph; Bergman, Anders; Eriksson, Olle; Pereiro, Manuel
Abstract: In magnetic materials, nontrivial spin textures may emerge due to the competition among different types of magnetic interactions. Among such spin textures, chiral magnetic solitons represent topologically protected spin configurations with particle-like properties. Based on atomistic spin dynamics simulations, we demonstrate that these chiral magnetic solitons are ideal to use for logical operations, and we demonstrate the functionality of a three-input majority gate, in which the input states can be controlled by applying an external electromagnetic field or spin-polarized currents. One of the main advantages of the proposed device is that the input and output signals are encoded in the chirality of solitons, that may be moved, allowing to perform logical operations using only minute electric currents. As an example we illustrate how the three input majority gate can be used to perform logical relations, such as Boolean AND and OR.